Impact of Strict Isolation Precautions on Families with a Language Other than English - Polina Frolova Gregory; Sanyukta Desai; Corrie E. McDaniel; Austin DeChalus; Emily Bowen; Michael Dinh; Jessica Gagen; Dwight Barry; Abena Knight; Matthew Test; Arti D. Desai; Mersine A. Bryan (Health Equity)
Introduction: Children with a language for care other than English (LOE) are at risk for inequitable care. We examined the association of isolation precautions in the care of hospitalized children with LOE through the frequency of professional interpreter use and timing of in-person consultation. Methods: Retrospective cohort study of children in a strict isolation unit (SIU) between 2/2020 and 12/2021. Negative binomial regression was used to assess both differences in interpretation rates between SIU and non-SIU, and within 72-h/in-person consultation rates within the SIU between English-speaking and LOE encounters. Results: We identified 487 encounters in the SIU; 126 (26%) involved patients with LOE. The median interpretations per day were 4.5 (Interquartile Range [IQR]: 2.0–6.7). Among patients with LOE, there was an observed difference in median interpretations per day in the SIU (3.9, IQR: 1.7–6.4) versus encounters in non-SIU acute care units (5.0, IQR: 1.2–8.2). However, this difference was not statistically significant (Incidence Rate Ratio [IRR]: 0.89; 95% confidence interval [CI]: 0.70–1.13). Sub-specialty consultations were requested for 410 (84%) encounters within the SIU; 282 (69%) were completed in person within 72 h. A small difference between the percentage of completed consultations for encounters with LOE (n = 61, 64%) and English-speaking patients’ encounters (n = 221, 70%) was noted, which again was not statistically significant (IRR: 0.93; 95% CI: 0.71–1.21). Conclusion: Despite the increased barriers of strict isolation, we exceeded institutional standards for interpretations per day and had similar rates of interpretation for encounters with LOE admitted to medical units regardless of isolation status.